Cost and state-of-the-art about fuel cells technologies - Rodriguez, Coronado C.; Bollini, Braga. L.; Luz, Silveira. J. (Revista Ciências Exatas, 2009)
The hydrogen is a form of alternative energy to fossil fuels that has been considered like new power vector for a future not far distant. Its use in fuel cells allows, together with oxygen or air to conversion for electricity or thermal energy in a clean and efficiency way, being able to be used in stationary facilities (for example, residences, business, etc; using cogeneration’s methods) or in the automobilist sector. The great advantages of the use of hydrogen like power vector, in case of ethanol (Brazilian market), it allows an increase of the participation of alternative energies and the reduction of the greenhouse gas discharges and another polluting atmospherics that affect the main urban centers. In this work a state-of-the-art of the technologies of fuel cells available in the worldwide market will appear; its applications, state of technological development and the main companies of the world-wide market. One will also appear some data of costs of investment (US$/kW) and values of useful life of systems with fuel cells in order of becoming such technologies in alternatives commercially available. One concludes with a detailedb description of systems of fuel cells available in the market with emphasis to the Polymer Elctrolyte Membrane Fuel Cell.